PRINSIP HUKUM EKONOMI ISLAM: MEMAHAMI LARANGAN RIBA DI ERA RASULULLAH - ninis fitriani; Arya Duta Al Hajry; Ahmad Mu’is (Lisyabab : Jurnal Studi Islam dan Sosial, 2025)
This article discusses the prohibition of riba in Islamic economic law during the era of Prophet Muhammad (peace be upon him). Riba is considered a detrimental practice that fosters injustice within society. This study employs a qualitative descriptive approach through a literature review of the Qur'an, Hadith, and classical fiqh sources. The research highlights two main types of riba: riba nasi’ah and riba fadhl. Riba nasi’ah was commonly practiced during the pre-Islamic era and involves additional interest due to delayed payment. Meanwhile, riba fadhl refers to the exchange of similar goods in unequal quantities. The findings indicate that the prohibition of riba was established to protect the economic welfare of the Muslim community and to uphold the principles of justice.